Release of excessive iron concentration from human blood and urine of cigarette smokers by using cystus-sud - Wan Mohd Azhar, Ibrahim; Syed Fahad Akbar Ali; Muhammad Asif; Eraj Humayun, Mirza (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/